Multi-Chamber Graves from the Tell el-Farkha Cemeteries - Karolina Rosińska-Balik (Ksiegarnia Akademicka Publishing, 2013)
The Tell el-Farkha cemeteries demonstrate the typical burial customs of their periods. From the 120 burials discovered so far, one can distinguish two main types of graves, namely a simple grave pit or a pit lined with mud bricks. The latter has various subtypes including multichamber graves. This interesting group, small in number, reveals unusual funeral practice, which was probably connected with the social position of the deceased. In this paper, the multi-chamber group is presented with all its differences and similarities.